DEPENDENCE OF FIRST-YEAR STUDENTS’ MOTIVATION ON THE CHOSEN AREA OF TRAINING OR SPECIALTY - O. I. Krushelnitskaya; M. V. Polevaya (Высшее образование в России)
The purpose of the study is to identify the peculiarities of the motivation for obtaining higher education by modern first-year students, including those depending on the chosen area of training (specialty). The students of the first courses of 12 universities and branches of Russia from different regions of Russia took part in the study. The students estimated the relative importance of motives by direct ranking. The study has identified the motives which are the most significant for freshmen of all training areas, and which are the least significant. There were revealed special features of the motivation of freshmen of each of the training areas. The features of motivation of first-year students who have chosen this or that direction of preparation are in close connection with the social and economic situation in the country, and reflect not only the subjective aspirations of students, but also their real expectations. The quantitative data obtained in this study can be used as a basis for analyzing the structure of motivation for higher education.